Exogenous noggin binds the BMP‐2 receptor and induces alkaline phosphatase activity in osteoblasts. Issue 8 (19th March 2019) - Hashimi, Saeed M.
Abstract: Osteogenesis is an important process in bone remodeling and is under strict cellular signaling governed by growth factors and antagonists. Bone morphogenetic protein 2 (BMP‐2) is an important osteogenic factor involved in the transcription of key osteogenic genes such as alkaline phosphatase (ALP). While, antagonists such as noggin effectively restrict osteoblast differentiation through binding to BMP‐2. In this study, we sought to understand the effect of exogenous noggin in osteoblasts and its role in BMP‐2 activation of osteogenesis. Enzymatic activity of ALP was monitored to ascertain the effect of the noggin. Fluorescently labelled noggin was used to determine the binding of noggin to the BMP‐2 receptor. The results demonstrated that noggin significantly increases the activity of ALP at concentrations of 50 to 400 ng/mL. While, it inhibited the activity of exogenous BMP‐2. Furthermore, fluorescently labelled noggin showed strong binding to osteoblasts which were perturbed when cells were preincubated with BMP‐2 suggesting that noggin shares a common receptor with BMP‐2. These results suggest that exogenous noggin facilitates osteogenic differentiation and provide a novel mechanism for its interplay with BMP‐2. Abstract : In this study, we sought to understand the effect of exogenous noggin in osteoblasts and its role in bone morphogenetic protein 2 (BMP‐2) activation of osteogenesis. Our results show that in the presence of BMP‐2, noggin has an inhibitory effect on osteogenesis and when BMP‐2 is absent, noggin binds to the BMP‐2 receptor and activates enzymatic alkaline phosphatase (ALP) activity. Our results show that further studies are required to ascertain the importance of noggin through its binding to the BMP‐2 receptor.